2019
DOI: 10.1002/pro.3674
|View full text |Cite
|
Sign up to set email alerts
|

β‐Amyloid aggregation and heterogeneous nucleation

Abstract: In this article, we consider the role of heterogeneous nucleation in β‐amyloid aggregation. Heterogeneous nucleation is more common and occurs at lower levels of supersaturation than homogeneous nucleation. The nucleation period is also the stage at which most of the polymorphism of amyloids arises, this being one of the defining features of amyloids. We focus on several well‐known heterogeneous nucleators of β‐amyloid, including lipid surfaces, especially those enriched in gangliosides and cholesterol, and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 195 publications
(337 reference statements)
2
62
0
4
Order By: Relevance
“…αS, given its amphipathic nature, prompts a preferential adsorption at hydrophobic/hydrophilic interfaces in order to simultaneously maximize the hydrophilic interactions in the aqueous environment and the hydrophobic force at the hydrophobic surface 7 , and there, we and others have observed that the protein is able to nucleate the formation of amyloid aggregates 6,8 . Indeed, hydrophobic/hydrophilic interfaces have been found to be critical for the aggregation of many other amyloidogenic proteins and peptides that also share the amphiphilic character with αS, including disordered peptides such as amyloid β (Aβ peptide 74 and folded proteins such as insulin 75 . Under more limited hydration conditions, however, we have observed that the nucleation process becomes favored, even at low micromolar protein concentrations (Fig.…”
Section: Limited Hydration Conditions Are Required To Trigger Nucleatmentioning
confidence: 99%
“…αS, given its amphipathic nature, prompts a preferential adsorption at hydrophobic/hydrophilic interfaces in order to simultaneously maximize the hydrophilic interactions in the aqueous environment and the hydrophobic force at the hydrophobic surface 7 , and there, we and others have observed that the protein is able to nucleate the formation of amyloid aggregates 6,8 . Indeed, hydrophobic/hydrophilic interfaces have been found to be critical for the aggregation of many other amyloidogenic proteins and peptides that also share the amphiphilic character with αS, including disordered peptides such as amyloid β (Aβ peptide 74 and folded proteins such as insulin 75 . Under more limited hydration conditions, however, we have observed that the nucleation process becomes favored, even at low micromolar protein concentrations (Fig.…”
Section: Limited Hydration Conditions Are Required To Trigger Nucleatmentioning
confidence: 99%
“…This feature has been indeed used to develop other strategies of inducing aggregation, such as the addition of hydrophobic nanoparticles [86], or larger beads [87], or even lipid vesicles composed of particular (typically non-physiological) types of phospholipids, which have resulted in good nucleation-active surfaces [88,89]. Interestingly, this is not a unique property of αS, since hydrophobic/hydrophilic interfaces have been found to be critical for the aggregation of many other amyloidogenic proteins and peptides, including IDPs such as the Aβ peptide [90], and folded proteins such as insulin [91]. We have recently observed, however, that αS can form amyloid aggregates without the need of a nucleation-active surface through homogeneous nucleation under limited hydration conditions, and that when the protein undergoes this process, there is a preference for remarkably different amyloid polymorphs.…”
Section: Primary Nucleationmentioning
confidence: 99%
“…One catalytic pathway is called seeding, where adding a preformed nucleus (seed/prion) enables the system to completely bypass the nucleation step and move directly to the growth or elongation step (Eisenberg and Jucker, 2012). The other important catalytic pathway is the heterogeneous nucleation mechanism (HEN), where an exogenous surface catalyzes the nucleation process (Buell, 2017;Srivastava et al, 2019). In HEN, the surface lowers the energy barrier to nucleation and acts as a scaffold that facilitates nucleus formation via binding, concentrating and enabling conformational changes in the bound proteins (Auer et al, 2009;John et al, 2018; Figure 1).…”
Section: Amyloid Nucleation Mechanismsmentioning
confidence: 99%
“…The nucleation barrier dictates whether a protein would spontaneously form an amyloid via HON or whether it requires a catalytic event, which can be a preformed seed/prion or an exogenous surface (HEN). In addition, together with other environmental factors such as pH and ion concentration, it affects the final polymorphic superstructure (Srivastava et al, 2019).…”
Section: A Mechanistic Approach To Etiologymentioning
confidence: 99%